THE RELATIONSHIP OF SELF-RESILIENCE TO THE ACADEMIC PERFORMANCE OF STUDENTS OF THE FACULTY OF MEDICINE, UNIVERSITY OF MUHAMMADIYAH SURABAYA DURING THE COVID-19 PANDEMIC - Djatmiko Diva Talitha Raissa; Yuliyanasari Nurma; Yelvi Levani (Universitas Muhammadiyah Surabaya, 2023)
The rise of covid-19 pandemic cases in Indonesia has caused physical and psychological changes, especially in medical students. In addition, the learning activities of medical students have also changed, due to the lockdown and quarantine, so that learning is carried out online. Medical students must be able to adjust to this learning. This ability is called self-resilience. Because medical students are prone to psychological stress and followed by low self-resilience. High levels of stress can affect concentration, academic performance and cognitive function. Research on self-resilience has never been carried out at the Faculty of Medicine, University of Muhammadiyah Surabaya during the Covid-19 Pandemic.Knowing the Relationship between Self-Resilience and Academic Performance of Students of the Faculty of Medicine, University of Muhammadiyah Surabaya during the Covid-19 Pandemic. This study used an observational analytical method with a cros sectional approach. Data collection is carried out by requesting an ethics permit letter. With the population of all students of the Faculty of Medicine, University of Muhammadiyah Surabaya class of 2018-2021 with a total of 307 students and a sample of 183 students. Statistical test technique using spearmen test. Based on the results of the spearmen test of the relationship of self-resilience to the academic performance of students of the Faculty of Medicine, University of Muhammadiyah Surabaya during the Covid-19 pandemic, a p value of < 0.05 and a value of r = -0.28 were obtained. There is no Relationship between Self-Resilience and Academic Performance of Students of the Faculty of Medicine, University of Muhammadiyah Surabaya during the Covid-19 Pandemic.Keywords: Self-resilience, academic performance, covid-19